PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS DAN DANA BAGI HASIL TERHADAP BELANJA MODAL PADA PEMERINTAH DAERAH KABUPATEN/KOTA DI PROVINSISULAWESI TENGAH - Rifai, Rachmawati A. (Katalogis, 2017)
The purposes of this study are: 1) to capture the development of regional revenue, general allocation funds, specific allocation funds, and profit sharing funds on capital expenditure at the district/city governments in Central Sulawesi; 2) to determine and analyze the simultaneous influence of regional revenue, general allocation funds, specific allocation funds, and profit sharing funds on capital expenditure at the district/city governments in Central Sulawesi; 3) to determine and analyze the partial influence of regional revenue, general allocation funds; specific allocation funds, and profit sharing funds on capital expenditure at the district/city governments in Central Sulawesi. The method of research is descriptive verification with multiple regressions analysis. Sample in this study involves all disctricts and cities in Central Sulawesi with a period of study for four years, from 2010-2014. The results show that the contribution of regional revenue, general allocation funds, specific allocation funds, and profit sharing funds on capital expenditure at the district/city governments in Central Sulawesi is 44.6%; 55.4% is influenced by other variables. Simultaneously, regional revenue, general allocation funds, specific allocation funds, and profit sharing funds have significant influence on capital expenditure at he district/city governments in Central Sulawesi. Partially, specific allocation funds as significant influence on capital, while regional revenue, general allocation funds, and profit sharing funds have insignificant influence on capital expenditure at the district/city governments in Central Sulawesi. Â